2009
DOI: 10.1002/humu.20882
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and polymorphisms in the proprotein convertase subtilisin kexin 9 (PCSK9) gene in cholesterol metabolism and disease

Abstract: Hypercholesterolemia is one of the major causes of coronary heart disease (CHD). The genes encoding the low-density lipoprotein receptor and its ligand apolipoprotein B, have been the two genes classically implicated in autosomal dominant hypercholesterolemia (ADH). Our discovery in 2003 of the first mutations of the proprotein convertase subtilisin kexin 9 gene (PCSK9) causing ADH shed light on an unknown actor in cholesterol metabolism that since then has been extensively investigated. Several PCSK9 variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
145
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(158 citation statements)
references
References 87 publications
3
145
0
10
Order By: Relevance
“…Human genetic studies have suggested that the residues in this region modulate PCSK9 function (6,13,42). Experimental data further showed that deletion of residues 31-53 significantly increases the affinity of PCSK9 for LDLR (30) and that the acidic residues in this region contribute to the effect (32).…”
Section: Discussionmentioning
confidence: 99%
“…Human genetic studies have suggested that the residues in this region modulate PCSK9 function (6,13,42). Experimental data further showed that deletion of residues 31-53 significantly increases the affinity of PCSK9 for LDLR (30) and that the acidic residues in this region contribute to the effect (32).…”
Section: Discussionmentioning
confidence: 99%
“…6,7,15,16 After the discovery of PCSK9 and its relationship to circulating levels of LDL-cholesterol (LDL-C), 12,14 a race was sparked around the world to find not only new gain-of-function (GOF) mutations causing hypercholesterolemia 14,17 but also loss-of-function (LOF) mutations compatible with hypocholesterolemia. 18,19 The highly active Anglo-Saxon D374Y PCSK9 variant is the most remarkable GOF mutation,…”
mentioning
confidence: 99%
“…We also show the biological application of 2',4'-BNA NC -modified oligonucleotides to reduce expression level of target mRNA in mammalian cells [14]. PCSK9 is a serine protease involved in the degradation of LDL receptor [15][16][17]. Suppression of PCSK9 by reducing expression level of PCSK9 mRNA may cause an increase in the amount of the LDL receptor, resulting in the reduction of serum LDL cholesterol level.…”
Section: Introductionmentioning
confidence: 92%